Image Watermarking Based On DWT, DCT and SVD Techniques (International Journal of Engineering and Computer Science, 2015)
Digital watermarking is a technique used for the information of the images that provides security for the confidentiality. The repetitions of the multimedia objects (i.e. audio, video, text, etc.) have been protected by some of the developed digital watermarking techniques. In this paper, we propose discrete wavelet transform (DWT), discrete cosine transform (DCT) and singular value decomposition (SVD) to protect duplication of digital media efficiently and used for digital watermarking images. SVD is applied to the approximate and the vertical coefficient of wavelet transform improves image protection in terms of PSNR and MSE between original and watermarked images. Experimental results show that the proposed algorithm give good imperceptibility for images and provides a watermarked images with good quality.